Development of Project Based Learning STEAM based Water Purifier Educational Kit on Water Pollution to Train Critical Thinking Skills - Sari, Shinta Permata; Nugraheni*, Dian; Hamimi, Erti; Pratiwi, Novida; Habiddin, Habiddin (Universitas Syiah Kuala, 2025)
Critical thinking skills are one of the skills needed in the 21st century. In one of the junior high schools in Pasuruan, students' critical thinking skills are low, so they still need improvement. The goal of this research was the creation of a learning media for an educational kit based on PjBLSTEAM that is considered worthy of being tested for its validity, practicality, and effectiveness in training junior high school students' critical thinking skills on water pollution material. The development procedure was based on the ADDIE model (analyze, design, develop, implement, and evaluate) with data collection techniques using interviews, questionnaires, and pretest-posttest questions. Data analysis techniques were applied using qualitative descriptive techniques, percentage analysis, validity tests, practicality, and effectiveness tests from the paired sample Ttest and N-Gain tests. The results of the media and material validation tests were shown to meet very valid criteria. The results from the teachers and students' feedback showed a very practical percentage. The media was considered effective, as evidenced by the results of the paired sample t-test, which indicated a difference in students' critical thinking scores before and after treatment, and the N-Gain test results, which showed a medium bar value. This research indicates that the learning media developed was valid, practical, and effective for training students' critical thinking skills